Research on Improving Online Purchase Intention of Poverty-Alleviation Agricultural Products in China: From the Perspective of Institution-Based Trust - Li, Guangming; Wu, Xianghua; Yuan, Chao (Frontiers in Psychology, 2022)
Poverty alleviation by consumption is a powerful way to help the poor people get rid of poverty, which plays a significant role in China's rural revitalization. However, the achievement of poverty alleviation by consumption mostly depends on government procurement, and the enthusiasm of customers to participate is low, facing the severe challenge of poor sustainability. Helping the poor is the most common motivation for customers to buy poverty-alleviation agricultural products (PAAP). However, as the negative events of poverty alleviation such as “tragic marketing” constantly appear in news reports, customers' trust in sellers has been seriously damaged. The psychological protection system for fear of being cheated hinders customers' purchase intention. Therefore, we believed that trust is an important factor in enhancing customers' purchase intention of PAAP. Customers buy PAAP mainly through online channels, and institution-based trust is the most important way to generate trust in online channels. Thus, this study investigated the institutional mechanisms that affect customers' trust in the sellers of PAAP and discussed the influence of trust on the online purchase intention of PAAP. Data were obtained through a questionnaire survey and tested empirically. The results showed that the effectiveness of the user feedback mechanism, platform supervision mechanism, product traceability mechanism, and product certification mechanism can enhance customers' purchase intention by enhancing their trust. Individual trust tendency positively regulated the relationship between the effectiveness of institutional mechanisms and consumer trust. The conclusion can not only provide new theoretical guidance for the practice of poverty alleviation by consumption in China but also offer new ideas for the poverty alleviation undertakings in other countries.